Deciphering Melasti Beach’s Tourism Development: A Tourism Area Life Cycle Study - Ahmad Irfan Ardiansyah; Aulia Amatullah; Ika Laily Lailatun Munasifah; Fatiya Rosyida; Alfi Sahrina (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Melasti Beach Ungasan has rapidly developed as a popular nature-based tourist destination in South Bali since its inception in 2018. As tourism grows, it becomes crucial to evaluate its development and identify sustainable management strategies. Previous studies on tourism development often focus on infrastructural growth or community involvement but rarely integrate both aspects using a systematic model. This research fills that gap by employing the Tourism Area Life Cycle (TALC) model to analyze the development stage of Melasti Beach Ungasan and assess its tourism characteristics, such as facilities, attractions, visitor trends, and local community involvement. A qualitative approach was used, with primary data gathered through field observations during the first field trip on October 11th, 2023, and secondary data from relevant literature. Descriptive-qualitative analysis reveals significant infrastructural improvements, such as the addition of parking facilities, beach clubs, and MSME kiosks. According to the TALC model, Melasti Beach is positioned between the “involvement” and “development” stages, characterized by increasing collaborations, seasonal tourism, and enhanced modern facilities. This research highlights the importance of protecting natural and socio-cultural assets while promoting active community engagement in tourism management. These factors are vital to ensuring the long-term sustainability of Melasti Beach Ungasan as a tourist destination.